PsycEXTRA Dataset 2011
DOI: 10.1037/e741382011-288
|View full text |Cite
|
Sign up to set email alerts
|

The roles of shame and guilt in hypersexual behavior

Abstract: Studies among people struggling with hypersexual behavior commonly report that shame needs to be addressed when treating this population. These studies theoretically distinguish that it is shame and not guilt that exacerbates hypersexual behavior, yet no study to date has demonstrated this difference empirically. This observation led to the current investigation in which a sample (N = 177) of people seeking treatment for pornography use anonymously filled out measures of hypersexuality, shame-proneness, guilt-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 17 publications
3
41
0
3
Order By: Relevance
“…Taken together, these findings point to a possibility that sexual conservatism underpins the perception of control over one's sexuality, likely working through shame and/or guilt [43]. However, due to cross-sectional character of our study, it is unclear whether the observed psychological maladjustment is an outcome or a precursor of the lack of control over one's sexuality and the associated negative consequences.…”
Section: Discussionmentioning
confidence: 65%
“…Taken together, these findings point to a possibility that sexual conservatism underpins the perception of control over one's sexuality, likely working through shame and/or guilt [43]. However, due to cross-sectional character of our study, it is unclear whether the observed psychological maladjustment is an outcome or a precursor of the lack of control over one's sexuality and the associated negative consequences.…”
Section: Discussionmentioning
confidence: 65%
“…57, September, 2018 BUTLER, MELOY-MILLER, SEEDALL, & DICUS / 829 beneath you," and inviting change, the anger pathway from an inflated SIRO tends to precipitate "you are a terrible person" attacks. Inflated SIRO anger produces such covert and overt character attacks that risk evoking toxic shame rather than creating a productive behavioral guilt (Gilliland, South, Carpenter, & Hardy, 2011). Ironically, far from leveraging offender change in a heavy-handed way, such tactics profoundly undermine change (Gilliland et al, 2011;Miller & Rollnick, 2002).…”
Section: Analysis Of the Anger Pathway Of Inflated Siromentioning
confidence: 99%
“…Inflated SIRO anger produces such covert and overt character attacks that risk evoking toxic shame rather than creating a productive behavioral guilt (Gilliland, South, Carpenter, & Hardy, 2011). Ironically, far from leveraging offender change in a heavy-handed way, such tactics profoundly undermine change (Gilliland et al, 2011;Miller & Rollnick, 2002). Third, hostile anger and attendant retribution compound and complicate relational resolution, multiplying injuries and amplifying offenses.…”
Section: Analysis Of the Anger Pathway Of Inflated Siromentioning
confidence: 99%
“…We additionally argue that unrestricted sex drive among regularly cheating people might be related to a slight decrease in guilt-proneness in a long run. Although high sex drive did not correlate with guilt-proneness in a study by Gilliland, South, Carpenter, and Hardy (2011), their sample consisted of men characterized by hypersexual behavior of rather unsatisfied sex drive. This discernibly differs from adults whose sex drive is very high, but satisfied thanks to a larger history of cheating.…”
Section: Discussionmentioning
confidence: 74%